Moco de pavo: desistimiento y novela (XXI Century. Spanish Literature and Culture, 2005)
Essay that studies the situation of the current novel that is suffering from withdrawal, orfinishing of art. Reflect on the changes that postmodernity and artcontemporary have made on the way of conceiving art in general and on thenovel in particular.
Keywords: novel; postmodernism; González Sáinz